2007
DOI: 10.1289/ehp.10294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic and Acute Ozone Exposure on Lipid Peroxidation and Antioxidant Capacity in Healthy Young Adults

Abstract: BackgroundThere is growing evidence for the role of oxidative damage in chronic diseases. Although ozone (O3) is an oxidant pollutant to which many people are exposed, few studies have examined whether O3 induces oxidative stress in humans.ObjectivesThis study was designed to assess the effect of short-and long-term O3 exposures on biomarkers of oxidative stress in healthy individuals.MethodsBiomarkers of lipid peroxidation, 8-isoprostane (8-iso-PGF), and antioxidant capacity ferric reducing ability of plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 45 publications
3
59
2
Order By: Relevance
“…However, systemic oxidative stress may be better reflected by 8‐epi‐PGF 2α measured in plasma or urine. Mixed results have been seen between air pollution and 8‐epi‐PGF 2α 26, 35, 36 or other oxidative stress markers 37…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic oxidative stress may be better reflected by 8‐epi‐PGF 2α measured in plasma or urine. Mixed results have been seen between air pollution and 8‐epi‐PGF 2α 26, 35, 36 or other oxidative stress markers 37…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that short-term ozone exposure is associated with decrements in lung functions, increased respiratory symptoms, and lung inflammation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The effect of short-and long-term ozone exposure was associated with biomarkers of oxidative stress (26), and with reduced heart rate variability (27). Finally, a review of toxicologic studies found decreased heart rate, metabolism, blood pressure, and cardiac output when rats are exposed to typical concentrations of ozone (28).…”
mentioning
confidence: 99%
“…Chen et al (2007) observed that long-term exposure to ozone as an atmospheric pollutant led to significant correlation with increases in lipid peroxidation. According to the findings from this study, 8-isoprostane 98-iso-PGF was found to be a good biomarker of oxidative damage related to air pollution.…”
Section: Oxidative Stress and Chronic Diseasesmentioning
confidence: 99%